Hardness and adhesion performances of nanocoating on carbon steel - J. N., Hasnidawani; Hassan, Noor Azlina; Hassan, Norita; Bonnia, Noor Najmi (Institute of Physics Publishing, 2018)
Nanocoatings industry has been aggressive in searching for cost-effective alternatives and environmental friendly approaches to manufacture products. Nanocoatings represent an engineering solution to prevent corrosion of the structural parts of ships, insulation and pipelines industries. The adhesion and hardness properties of coating affect material properties. This paper reviews ZnO-SiO2 as nanopowder in nano coating formulation as the agent for new and improved coating performances. Carbon steel on type S50C used as common substrate in nanocoating industry. 3wt% ZnO and 2wt% SiO2 addition of nanoparticles into nanocoating showed the best formulation since hardness and adhesion of nanocoating was good on carbon steel substrate. Incorporation of nanoparticles into coating increased the performances of coating.